The development of value for money (vfm) assessment tool for public private partnership (ppp) approach - Takim, Roshana; Nawawi, Abdul Hadi; Ismail, Kharizam (2012)
Primarily value for money in public private partnership projects can be defined as the optimum combination of whole life cost and quality to meet the user's requirement. Based on the contingency theory, value for money is abroad term that captures both elements of financial and non-financial aspects in the evaluation. Several diverse approaches to assess value for money had been applied in different countries. Nevertheless, value for money assessment method has been criticised on numerous grounds with respects to: accuracy of risk transfer; discount rate methodology; limitation scope of non financial and consideration of long term evaluation. For these reasons, the research aim is to draw a complete value for money assessment tool (financial and non-financial aspects) by means of 2 objectives (1) to investigate the criteria to be integrated in the evaluation of PPP bids for value for money, and (2) to identify the elements at each stage of PPP in the value for money assessment process. Two methods of empirical research via questionnaire survey and case study (semi structured interview) were conducted among PPP stakeholders. In total 216 valid responses were received, constituting a response rate of 23.6%. The result were analysed by descriptive and analytical statistical analysis (ANOVA). In order to underpin the questionnaire survey, three case study were conducted by using structured interview with government body, consultants and contractors. The results revealed that the nine criteria of Public Private Partnership bids for value for money are: optimum whole life cost; innovation; comprehensive specification, environmental aspects, user benefit, integrated planning and design, fit for purpose, risk allocation and facilities management. In addition, the respondents believed that financial and non-financial aspects are vital elements to be captured in the development of value for money assessment methods at each phase of PPP project life cycle. The research output would facilitate a comprehensive dimension of VFM assessment tool for PPP projects in Malaysia and provide high significant impact to the government, consultants and contractors as PPP stakeholders.